HEALTH EDUCATION USING MATCHING IMAGES TO ENHANCE PRESCHOOLERS’ KNOWLEDGE ON FRUITs AND VEGETABLES - Alfonsa Reni Oktavia; Ricca Olivia Nastasya; Dwi Ayu Lestari; Dewi Susanti; Bias Talenta (Bajang Institute, 2024)
WHO suggests that people of all ages should consider increasing their intake of fruit and vegetables. It has a positive impact on learning potential and wellbeing in children and adolescents.The consumption of vegetables and fruit by children is influenced by parental knowledge and motivation. The use of educational nutrition games with puzzle-based learning aims to enhance children''s understanding and reduce the sense of obligation. Tthe consumption of vegetables and fruit by children is relatively low in early childhood education in Kebayoran Lama the research project entitled